Answer:
1) 4, -5 and 3 are the ZEROES of the expression j = (p - 4)(p + 5)(p - 3)
Step-by-step explanation:
Here, the given phrase is:
j = (p - 4)(p + 5)(p - 3)
Now, here j is Expressed as the product of roots.
(p - 4),(p + 5) and (p - 3) are 3 given roots of the polynomial j.
Now, if (x-a) is the ROOT of the polynomial, then x = a is the ZERO of the POLYNOMIAL.
In this given expression:
(p-4) is the ROOT⇒ 4 is the ZERO of the polynomial j.
(p+5) is the ROOT⇒ (-5) is the ZERO of the polynomial j.
(p-3) is the ROOT⇒ 3 is the ZERO of the polynomial j.
Hence, here 4, -5 and 3 are the ZEROES of the expression
j = (p - 4)(p + 5)(p - 3)